Influence of age, sex and somatic variables on the motor performance of pre-school children. (September 2013) - Saraiva, Linda; Rodrigues, Luís P.; Cordovil, Rita; Barreiros, João
Abstract Background: Biological factors can affect the motor development process of children. However, the magnitude of these effects throughout the developmental process remains fairly unknown. Aim: To determine the influence of age, sex and selected somatic measures on the motor performance of pre-school children. Subjects and methods: Three hundred and sixty-seven pre-schoolers (172 boys and 195 girls), aged from 3–5 years old, were recruited from 10 public pre-schools located in the district of Viana do Castelo, Portugal. The children's motor performance was assessed by five motor sub-tests of Peabody Developmental Motor Scales-2: grasping, visuo-motor integration, stationary, locomotion and object manipulation sub-tests. Age, sex, height, weight and BMI were considered as hypothetical predictors of motor performance. Pearson's correlation test and multiple linear regression analysis were used to explore the magnitude of the relationship between motor sub-tests and the hypothetical predictors. Results: Depending on the motor sub-test and age group, the models predicted motor performance from a minimum of 3.6% to a maximum of 34.4%. Age in months and sex stood out as the main predictors of motor performance. Conclusions: The relationship between motor performance and selected biological factors varied with age and with the specificity of the motor test.